Wireless Power Transfer to Sitallite Stratospheric Platform - Schubert, Peter J.; van Wynsberghe, Erinn; Kragt Finnell, Abigail J.; Salgueiro, Cristian; Suri, Ramaa Saket (IEEE International Conference on Wireless for Space and Extreme Environments conference digest (Online), 2020)
Stratospheric superpressure balloons are a class of high-altitude pseudo-satellite (HAPS) with excellent observational and communications capabilities. The challenge to long-duration operation is station keeping against the thin but fast zephyrs at altitudes around 25 km. One solution is captured in the US patent 10,404,353, which describes a "Sitallite" HAPS having plasma air thrusters to maneuver against the wind. To hold station for months at a time requires a steady delivery of power, such as a microwave beam transmitted from a terrestrial phased array antenna (PAA) to a rectifying receiving antenna (rectenna) mounted on the underside of the superpressure balloon. This work explores the design and safety considerations for the wireless power transfer (WPT) aspects of such a Sitallite and the tradeoffs between array sizes and power requirements. Presented here are studies of the directivity of the PAA as a function of the number and spacing of antenna elements, and the expected impact on ground personnel, insects, birds, and overflying aircraft. The support and suspension structure of the high-altitude rectenna are developed, along with a comparison of various commercial Schottky diodes for this application. Finally, system studies are presented to illustrate the cost drivers and size optimization. Such a Sitallite can provide line-of-sight visibility for a 1,100 km radius, remain aloft for many months, and provide services normally expected from an orbiting satellite at a fraction of the cost.